Hemiparasites drive heterogeneity in litter arthropods: Implications for woodland insectivorous birds. (21st May 2019) - Mellado, Ana; Hobby, Annie; Lázaro‐González, Alba; Watson, David M.
Abstract: Providing fruit, nectar, leaves and litter, mistletoes represent important resources for many organisms, linking above‐ground patterns with below‐ground processes. Here, we explore how mistletoe litter affects arthropod availability, especially those taxa preferentially consumed by ground‐feeding insectivorous birds, a group that has undergone widespread declines. We estimated the influence of mistletoe on arthropod occurrence by sampling arthropod communities beneath infected and uninfected trees with pit‐fall traps. Then, we experimentally isolated direct effects of mistletoe litter on arthropods with a litterbag study. Soil arthropod communities beneath infected trees had consistently greater abundance and biomass – total arthropods and the subset of arthropods preferentially consumed by ground‐foraging insectivores – compared to otherwise comparable uninfected trees. Arthropods showed a weak response to litter addition, with maximum abundances recorded from bags with low mistletoe litter, significantly lower abundances associated with higher mistletoe fractions and pure tree litter (after 5 months). Our findings confirm that mistletoe occurrence has a significant positive impact on arthropod availability, especially on those preferred by ground‐foraging bird insectivores. However, only a minor part of this impact is due to the direct, short‐term effects of mistletoe litter, which suggests that additional mistletoe‐mediated effects (e.g. local changes in structural or microclimatic factors, cumulative effects over multiple years) play significant roles. By altering arthropod assemblages within leaf litter and increasing the heterogeneity of resource availability on forest floors, mistletoe plays an important role in improving habitat quality for declining insectivores. Abstract :